Hak-Hak Mitra Pembiayaan Murabahah di Bank Syariah - Muhammad Iqbal (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2019)
The purpose of this research is to learn how to carry out murabaha financing in Islamic banks and what are the rights and obligations of murabaha financing partners. Murabaha as a form of buying and selling mandate asks sellers and buyers to get to know each other and accept each other's bright buying objects, the agreed price, the desired margin, and the method of payment. Related to the price requested is the cost of goods and the cost of procurement in accordance with the price requested by the bank as the seller. While an explanation of the rights of murabaha financing partners is important it will not happen in the future. Bank Officers are required to be able to refute the theories of sharia contracts contained in the muamalah fiqh to avoid oversight in practice in Islamic banks. Because in reality, the average employee of a sharia bank has no Islamic economic background.